Arabic and English Conditional Clauses: A Comparative Study (The Eurasia Proceedings of Educational and Social Sciences, 2019)
According to a study done by Covitt (1976), Conditional sentences ranked fifth on a list of most serious teaching problems encountered by ESL teachers. Hence, this paper aims to conduct a comparative study of conditional clauses  in Arabic and English, to discuss some of the difficulties facing the students and English language learners in understanding the conditional structure and its translation from Arabic to English and vice versa. Conditional sentences and its structures are difficult sometimes become confusing for some students so they may become a puzzle that is hard to understand. Studying the conditional structure in general, and our understanding of its nature and the functions of its structure, helps us as educators and linguists to reach to our students' needs who find difficult to perform conditional clauses in Arabic and English and translated them correctly. Therefore, 40 lecturers had been asked about the difficulties in conditional clauses in order to focus on what should be done to analyze these difficulties encountered by students and language learners in the field of teaching in both Arabic and English. In this vein, the study aims to discuss the following aspects; first, the concept of conditional clauses and its classification in Arabic and English. Second, summarizes the similarities and differences of conditional clauses in both languages. Third difficulties that students face in learning conditional clauses and; finally, explore and clarify strategies for conditional clauses used to teach them to the students.
Keywords: Conditional clauses; Arabic; English; Strategies; Students